Art appreciation of the Malaysia independence day logo 2020 - Ibrahim, M.; Hashim, S.F.M.; Jamil, A.A.; Cob, S.A.C.; Omar, M.; Razali, H.M. (2021)
From the perception of Art Appreciation, requires two main aspects, namely formalistic and content. These two aspects come together to form a work of art. The logo is one of the results of art in the form of digital art that are always used in graphic design. This paper is conducted to identify the visual characteristic of the Malaysian Independence Day logo. Researchers only chose Independence Day for the year 2020 to be analyzed because it is the logo for the current year and is the latest logo design created compared to the previous two years using the same logo. To achieve the purpose, this method of this study is qualitative, which is to use the study of art appreciation evaluation analysis in the context of form and content. It clearly shows the formalistic aspects used in translating the literal and implicit meanings in the Independence Day 2020 logo. This logo features various artistic elements of art and principles of design, as described in this study. It also gives sense to the events that took place during the year. This study has combined the theoretical aspects of Formalistic art with graphic design that is the study of the Independence Day logo. A logo can be considered successful if all sections of society understand it. This logo is created every year, according to the theme and identity of the country. The logo design refers to the symbolism of a multiracial society that is pluralistic and dignified the culture in this country. Through the analysis that has been made, the creation of the Independence Day 2020 logo can be accepted because the logo is simple and easy to understand by the community. The use of the right logo can change people's perception of something.